Evaluate the Intentions and Behaviors of Live Streaming Feature Users with the UTAUT Model - Athallah Rafif Cahyono; Arista Pratama; Virdha Rahma Aulia (Komunitas Dosen Indonesia, 2025)
The rapid advancement of digital innovation in Indonesia's e-commerce industry has encouraged the widespread adoption of live streaming features such as Shopee Live, which enable real-time interaction between sellers and buyers. Despite the growing popularity of this feature, limited research has investigated the behavioral factors that drive its sustained use, particularly by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) with the construct of trust. This study aims to evaluate users’ behavioral intentions and actual usage of Shopee Live by applying the UTAUT model, extended with the trust variable to better capture the dynamics of live streaming-based commerce. A quantitative approach was employed through an online survey distributed to Shopee users with prior experience using the live feature. Using purposive sampling, a total of 215 valid responses were collected, with a response rate of 86%. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Effort Expectancy, Social Influence, Price Value, Habit, and Trust significantly affect behavioral intention, while Performance Expectancy, Facilitating Conditions, and Hedonic Motivation do not. Furthermore, Habit, Trust, and Behavioral Intention significantly influence actual usage behavior. This study contributes to the e-commerce literature by extending the UTAUT framework with trust in the specific context of live streaming. The findings emphasize the stronger role of trust and social factors over utilitarian and entertainment considerations. E-commerce platforms should focus on strengthening user trust, promoting ease of use, and encouraging habitual usage to increase engagement with live commerce features.